Evolutionary changes in plant reproductive traits following habitat fragmentation and their consequences for population fitness - Jacquemyn, Hans; De Meester, Luc; Jongejans, Eelke; Honnay, Olivier (The Journal of ecology, 2012)
1. The effects of habitat fragmentation on plant population genetic structure and diversity are relatively well studied. Yet, most of these studies used molecular tools focusing on neutral genetic markers, and much less is known about the potential evolutionary consequences of habitat fragmentation on ecologically relevant plant traits. 2. It can be expected that the altered biotic and abiotic conditions and limited gene flow following habitat fragmentation may impose strong selection pressures on traits important for plant fitness. Responses to these selection pressures may, however, be hampered by reduced genetic diversity through genetic drift. Conversely, evolutionary changes in flower or dispersal traits may itself impact the strength of inbreeding and genetic drift. 3. In this review, we highlight different reproductive plant traits that may be under selection following habitat fragmentation, and we examine studies that have shown indications for rapid evolutionary responses. 4. There are still relatively few studies that have convincingly shown that habitat fragmentation generates rapid evolutionary responses. Separating genetic from plastic trait responses and quantifying the long‐term fitness consequences of evolutionary changes in plant traits also remain major challenges. 5. Synthesis. Many plant traits may be subject to selection following habitat fragmentation, but, until now, studies that quantified evolutionary responses to habitat fragmentation are limited. To study the consequences of changing plant traits for population fitness, we advocate applying population models that link demographic vital rates, the responding plant traits and their heritability.